Developing Transformation Geometry Learning Media Integrated with The Architecture of Menara Kudus Mosque through an Articulate Storyline - Auliya, Nanang Nabhar Fakhri; Wahyuni, Fina Tri (Jurnal Pendidikan Matematika, 2024)
The objectives of this research are: 1) developing transformation geometry learning media integrated with the architecture of menara kudus mosque through articulate storyline; 2) knowing the feasibility of transformation geometry learning media integrated with the architecture of menara kudus mosque through articulate storyline. The research method used is the Research and Development (R & D) method with the ADDIE model stands for Analysis, Design, Development, Implementation  ,  Evaluation (evaluation/feedback). The results of this study were obtained, including: 1) the process of developing this learning media utilize several stages: a) analysis, conducting analysis of the mathematical lesson plan (in Indonesia called Rencana Pembelajaran Semester/ RPS), student needs, and characteristics; b) designing, planning mathematical topics structure, making flowcharts, preparing and evaluating mathematical topics, preparing a grid of media feasibility assessment instruments, media selection, media display planning stages; c) development, making applications in accordance with flowchat, media display plans and feasibility assessments to expert of learning media and mathematical content; d) implementation, conducting feasibility assessments to users (students). e)evaluation, revising the results of user assessment. 2) the results of the feasibility assessment of learning applications by expert of mathematical content obtained a percentage of 83% with eligibility criteria. The results of the assessment by expert of learning media were obtained 79.5% with feasible criteria.  The results of the assessment by users  (students) in the small group obtained 79.2% in the feasible category and in the large group obtained 76.83% in the feasible category. Tujuan dilakukannya penelitian ini yaitu: 1) mengembangkan aplikasi pembelajaran geometri transformasi terintegrasi arsitektur Masjid Menara Kudus berbantuan articulate storyline bagi mahasiswa tadris matematika; 2) mengetahui kelayakan aplikasi pembelajaran gemetri transformasi terintegrasi arsitektur Masjid Menara Kudus berbantuan articulate storyline bagi mahasiswa tadris matematika. Metode penelitian yang digunakan yaitu metode Research and Development (R&D) dengan model ADDIE singkatan dari Analysis (analisis), Design (desain/perancangan), Development (pengembangan), Implementation (implementasi/eksekusi), Evaluation (evaluasi/umpan balik). Diperoleh hasil penelitian dan pengembangan yaitu: 1) proses pengembangan aplikasi pembelajaran geometri-transformasi terintegrasi arsitektur Masjid Menara Kudus” berbantuan articulate storyline  dikembangkan dengan tahapan: a) analisis, melakukan analisis mencakup pemahaman materi, RPS, kebutuhan dan karakteristik mahasiswa; b) perancangan, melakukan perencanaan struktur materi, pembuatan flowchart, penyusunan dan evaluasi materi, penyusunan kisi-kisi instrumen penilaian kelayakan media, pemilihan media, tahap perencanaan tampilan media; c) pengembangan, membuat aplikasi sesuai dengan flowchat, rencana tampilan media dan penilaian kelayakan kepada ahli media, materi; d) implementasi, melakukan penilaian kelayakan kepada user (mahasiswa). e) evaluasi, melakukan revisi dari hasil penilaian user. 2) hasil penilaian kelayakan aplikasi pembelajaran oleh ahli materi diperoleh persentase sebesar 83% dengan kriteria layak. Hasil penilaian oleh ahli media diperoleh 79,5% dengan kriteria layak.  Hasil penilaian oleh user (mahasiswa) pada kelompok kecil diperoleh 79,2% dengan kategori layak dan pada kelompok besar didapatkan 76,83% dalam kategori layak.